Inferiority and Compensation in the Main Character of Intan Paramaditha’s Short Story Perempuan Buta Tanpa Ibu Jari - Tifani Safira Mayasari; Ririe Rengganis (LPPM State University of Jakarta (Program Studi Pendidikan Bahasa dan Sastra Indonesia dan LPPM Universitas Negeri Jakarta), 2026)
This research is driven by the importance of understanding the representation of women's psychological experiences in contemporary Indonesian literature, which frequently portrays practices of social marginalization. A significant work in this field is the short story “Perempuan Buta Tanpa Ibu Jari